Perspektif Moral Penegakan Hukum yang Baik - Kusnu Goesniadhie S. (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research discusses about some rules related with the law’s establishment which is not only related with the body of law but also related with the nation’s institution, such as the compiling process to make a law’s constitution in Legislative institution and the protection for the public interest by the Executive institution. This research will excavate the good concept of law enforcement as the direct derivation of good governance concept. This research uses the concept of academic thinking and applies a good rule as has said in the frame of law’s comprehensibility. This is a theoretical explorative research. It uses the combination of normative method as well as theoretical method as the analysis method. The conclusion of this research is that good law enforcement needs an organized application in its process in order to gain the aimed goal which covers the actualization of value system that becomes the basis of attitude preference in the law enforcement, which is also aimed to the law’s intention.Key words : Legal moral, law enforcement, good governance